The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1111/iju.13705
|View full text |Cite
|
Sign up to set email alerts
|

Yonsei nomogram: A predictive model of new‐onset chronic kidney disease after on‐clamp partial nephrectomy in patients with T1 renal tumors

Abstract: We developed a novel nomogram for predicting the 5-year chronic kidney disease-free survival probability after on-clamp partial nephrectomy. This model might have an important role in partial nephrectomy decision-making and follow-up plan after surgery. External validation of our nomogram in a larger cohort of patients should be considered.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
14
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 33 publications
(122 reference statements)
1
14
1
Order By: Relevance
“…As for patients with comorbidities, previous studies showed that those with diabetes mellitus (DM) were more likely to develop CKD after nephrectomy. 16,28,29 While in our study, DM alone was not significantly associated with AKD. CCI is a weighted score for each of the comorbid conditions.…”
Section: Discussioncontrasting
confidence: 64%
See 1 more Smart Citation
“…As for patients with comorbidities, previous studies showed that those with diabetes mellitus (DM) were more likely to develop CKD after nephrectomy. 16,28,29 While in our study, DM alone was not significantly associated with AKD. CCI is a weighted score for each of the comorbid conditions.…”
Section: Discussioncontrasting
confidence: 64%
“…Previous studies have demonstrated that risk factors such as surgery approach, perioperative eGFR, complications, age, and sex were associated with AKI and CKD postoperatively. 15,16 However, as far as we know, the incidence rate and risk factors for AKD have not been studied and the prediction model for AKD after nephrectomy in RCC patients has not been established.…”
Section: Introductionmentioning
confidence: 99%
“…Second, this study only included surgeries that used minimally invasive laparoscopic or robotic techniques, and not open techniques. One study reported a lower risk of CKD in minimally invasive approaches [ 14 ], whereas others reported a similar risk [ 10 , 13 ]. However, minimally invasive approaches are being used more frequently for RN and PN [ 27 ]; thus, our model may be appropriate for future studies.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have investigated the predictive factors for CKD following RN or PN [ 9 16 ], some of which developed predictive models for CKD [ 13 , 14 ]. However, these studies analyzed preoperative and intraoperative factors (such as patient characteristics, preoperative laboratory values, and surgical type or technique) as possible predictors, without including postoperative laboratory values [ 9 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Abdel Raheem et al . reported a novel nomogram for new‐onset CKD after PN in patients with T1 renal tumors . This nomogram will play a prominent role in the selection of appropriate therapy and adequate follow up after PN in these patients.…”
mentioning
confidence: 99%